Pengembangan Bahan Ajar Berbasis Kearifan Lokal Riau Untuk Siswa Kelas IV Sekolah Dasar Pekanbaru - Ningrum Melihayatri; Zaka Hadikusuma Ramadan (Journal of Elementary School (JOES), 2021)
This study aims to develop teaching materials based on Riau local wisdom that are appropriate for thematic learning of theme 7 sub-theme 1. These teaching materials are expected to strengthen students' knowledge about local wisdom where students live, especially Riau. This research method uses development research with ADDIE development model. This research uses three stages. (1) the analysis phase is an analysis of the needs of teaching materials, curriculum analysis and situation analysis, (2) the design phase is to design the product according to the needs. In addition to designing product designs, researchers also developed research instruments, namely validation sheets, (3) the development stage, namely writing teaching materials, editing teaching materials, and testing validity. The results of this study indicate that the assessment of this teaching material expert category is very feasible with a percentage of 89%. The linguist's assessment of teaching materials is in the proper category with a percentage of 74.6%. The assessment of this teaching material design expert is a very feasible category with a percentage of 96.4%. Overall validation from material experts, linguists, and design experts is an average of 86.6% with very feasible criteria. Keywords: Teaching materials, Riau local wisdom, thematic